The Reproducibility of Indoor Air Pollution (IAP) Measurement: A Test Case for the Measurement of Key Air Pollutants from the Pan Frying of Fish Samples - Ki-Hyun Kim; Yong-Hyun Kim; Bo-Won Kim; Jeong-Hyeon Ahn; Min-Suk Bae; Richard J. C. Brown (The Scientific World Journal)
To assess the robustness of various indoor air quality (IAQ) indices, we explored the possible role of reproducibility-induced variability in the measurements of different pollutants under similar sampling and emissions conditions. Polluted indoor conditions were generated by pan frying fish samples in a closed room. A total of 11 experiments were carried out to measure a list of key variables commonly used to represent indoor air pollution (IAP) indicators such as particulate matter (PM: PM1, PM2.5, PM10, and TSP) and a set of individual volatile organic compounds (VOCs) with some odor markers. The cooking activity conducted as part of our experiments was successful to consistently generate significant pollution levels (mean PM10: 7110 μg m−3 and mean total VOC (TVOC): 1400 μg m−3, resp.). Then, relative standard error (RSE) was computed to assess the reproducibility between different IAP paramters measured across the repeated experiments. If the results were evaluated by an arbitrary criterion of 10%, the patterns were divided into two data groups (e.g., <10% for benzene and some aldehydes and >10% for the remainders). Most noticeably, TVOC had the most repeatable results with a reproducibility (RSE) value of 3.2% (n=11).